The world in the long twentieth century : an interpretation - Dickinson, Edward Ross (Oakland, California : University of California Press, 2017)
"The World in the Long Twentieth Century presents an interpretation of the history of the world in the century and a half between the middle of the nineteenth century and the beginning of the twenty-first. It identifies the most important forces shaping the interactions between world societies and regions, and the complex relationships between those forces and the events, ruptures, upheavals, and continuities they drove. The interactions between science and technology, economics, culture, and politics on the scale of world events and developments are analyzed, stressing the continuities and commonalities that made this entire period of some 150 years a coherent whole. Throughout the book, the emphasis is on the broad dynamics of world developments--the global trends and interactions that determined the course of events both locally, in individual societies, and on a global scale, in the patterns of interactions between regions, countries, and societies. The book places the period of revolutions, wars, and genocides in the early twentieth century in the context of the longer-term development of the world economy, world population, imperial politics on a global scale, and world-wide social and cultural changes between ca. 1850 and ca. 2010. That explosive period, it shows, was a product of the rapid economic, cultural, and political globalization of the late nineteenth century; and it laid the groundwork for the even faster globalizations of the late twentieth."--Provided by publisher.
The biological transformation of modern times -- The foundations of the modern global economy -- Reorganizing the global economy -- Localization and globalization -- The great explosion -- New world (dis)order -- High modernity -- Revolt and refusal -- Transformative modernity -- Democracy and capitalism triumphant.
Includes bibliographical references and index.
Keywords: History, Modern -- 20th century -- Chronology; History, Modern -- 21st century; World politics -- 20th century; World politics -- 21st century; Globalization -- Social aspects; Civilization -- 20th century